2022
DOI: 10.3390/economies10030065
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Perception of Audits, Access to Finance, and Self-Assessed Corporate Tax Compliance

Abstract: This study explores the influence of financial statement audits on tax compliance directly and indirectly through access to finance, and it examines gender roles to improve tax compliance through access to finance and financial statement audits. The sample for this study consisted of 45,504 businesses located in developing countries, as determined by The World Bank Enterprise Survey 2006–2018. The primary findings of this study demonstrate that the audit of financial statements has a positive impact on tax com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Authors concluded that women are less likely to cheat on taxes than men are, despite regional and cultural differences. Sunardi et al (2022) empirically examined implications of female top managers' presence regarding corporate tax compliance.…”
Section: Gender and Tax Compliancementioning
confidence: 99%
“…Authors concluded that women are less likely to cheat on taxes than men are, despite regional and cultural differences. Sunardi et al (2022) empirically examined implications of female top managers' presence regarding corporate tax compliance.…”
Section: Gender and Tax Compliancementioning
confidence: 99%